Biodiesel Production Using Reactive Distillation: Optimization And Comparative Simulation Study Using Aspen - Chuah, Jing Xuan (Universiti Sains Malaysia, 2021)
Depletion of fossil fuels in the recent years had led to attention of researcher to develop potential renewable energy as the fossil fuel substitute. Thus, biodiesel is suggested since it is a good replacement of fossil fuels as a ‘clean energy source’. However, due to high cost of raw material and operating expenses in conventional biodiesel production, biodiesel is considered not economically competitive compared to petroleum-based fuel. This limitation can be overcome by process intensification (PI) technology. PI technology is applied in intensified biodiesel production by using reactive distillation column to replace methanol recovery column and reactor. Reactive distillation (RD) is a process intensification technique that combines chemical reaction and distillation in a single equipment. To minimize the energy consumption in RD column, sensitivity and optimization analysis are conducted to study the effect of operating parameters such as feed temperature and reflux ratio on reboiler heat duty. Results from sensitivity analysis showed that reboiler heat duty is directly proportional to feed temperature but inversely proportional to reflux ratio. Optimized results showed that optimum condition for efficient production of biodiesel with minimum consumption of energy is at 145oC of feed temperature and reflux ratio at 1. Besides, the process gains obtained through intensification of a conventional biodiesel plant by addition of a reactive distillation column is studied. It is found that intensified process has higher conversion of Jatropha oil into biodiesel compared to conventional process with reported conversion rate at 48.19% and 32.52% for intensified and conventional process, respectively. From aspect of energy analysis, hot utility requirement in intensified process is 60.70% less than that required for conventional process with reported hot utility requirement at 7.702×104cal/s and 131.96×105 cal/s for intensified and conventional process, respectively. Besides, reboiler heat duty in intensified process is 21.84% less than in conventional process with reported reboiler duty at 69034.1kW and 88327.1kW for intensified and conventional process, respectively. From aspect of exergy analysis, result showed exergy change across reactor and methanol recovery column in conventional process are -10.39kW and -25.54kW, respectively. Whereas exergy change across reactive distillation column in intensified process is 91.15kW. This implies that exergy is lost or wasted in conventional process, whereas in intensified process exergy is gained within reactive distillation column. Thus, this reactive distillation column utilizes fully exergy gained from other sources.